2017
DOI: 10.1017/s0967199416000307
|View full text |Cite
|
Sign up to set email alerts
|

Seminal cell-free DNA levels measured by PicoGreen fluorochrome are associated with sperm fertility criteria

Abstract: Previous investigations suggested that elevated cell-free DNA (cfDNA) can indicate non-healthy states. However, the potential association between cfDNA seminal plasma levels and fertility sperm parameters has not yet been determined. Therefore, the present study evaluated the association between seminal cfDNA levels and sperm fertility criteria to determine the use of seminal cfDNA quantification. An in vivo protocol quantified cfDNA levels of semen samples obtained from 163 male patients using fluorescent Pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The dsDNA quantification has been used to evaluate inflammatory status of some chronic and infectious diseases, [43][44][45] and especially in sperm cells, high dsDNA levels have been associated with oxidative stress markers and infertility. 23,46 In one study reported by Costa et al, 47 the authors showed that sperm carrying homozygous SOD2 genotypes (AA and VV) have higher dsDNA levels than sperm with the AV genotype. Nonetheless, in our blood samples, basal dsDNA concentration was found to be higher in AA genotype subjects relative to VV genotype subjects, but only in AA genotype volunteers, did we notice a drop in the levels of this marker after BN ingestion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The dsDNA quantification has been used to evaluate inflammatory status of some chronic and infectious diseases, [43][44][45] and especially in sperm cells, high dsDNA levels have been associated with oxidative stress markers and infertility. 23,46 In one study reported by Costa et al, 47 the authors showed that sperm carrying homozygous SOD2 genotypes (AA and VV) have higher dsDNA levels than sperm with the AV genotype. Nonetheless, in our blood samples, basal dsDNA concentration was found to be higher in AA genotype subjects relative to VV genotype subjects, but only in AA genotype volunteers, did we notice a drop in the levels of this marker after BN ingestion.…”
Section: Discussionmentioning
confidence: 98%
“…Prior evidence revealed that higher levels of dsDNA in the plasma are associated with inflammatory and oxidative status due an increase in mortality of blood white cells, and Cadoná et al, 22 showed that pro-oxidant and antioxidant conditions can quickly change dsDNA concentrations because in a pro-oxidant environment, there could be an increase in the number of dead cells, whereas in an antioxidant environment, a delay in cell mortality may occur. Therefore, quantification of free plasma dsDNA was performed according to the protocol of Costa et al 23 Briefly, 10µl samples of plasma obtained from different volunteers were added into wells of a 96-well black plate together with reagents from the Quant-iT™ PicoGreen® Kit purchased from Invitrogen (Eugene, OR, USA) and diluted in TE buffer (10mm Tris-HCl, 1mm EDTA, pH 7.5) with reagents obtained from Sigma-Aldrich (St. Louis, MO, USA). Then, 90µl of the PicoGreen dye diluted 1:200 in Tris-HCl EDTA (TE) buffer was added to the microplate to attain a final volume of 100µl per well.…”
Section: Free Double-stranded Dna (Dsdna) Assaymentioning
confidence: 99%
“…DCFH-DA is a nonfluorescent chemical that is deacetylated by mitochondrial esterase enzymes to DCFH which reacts with ROS and becomes DCF, a fluorescent molecule. Fluorescence was recorded at an excitation wavelength of 488 nm and an emission wavelength of 525 nm [28]. NO levels were measured after 72 h by the Griess modified method [29].…”
Section: Methodsmentioning
confidence: 99%
“…The aforementioned average seminal cfDNA is notably higher than average blood cfDNA concentrations of PCa patients, being approximately 100 times higher compared to mean blood cfDNA values reported in literature (1.8-35 ng/μl). (Costa et al, 2017) In another study, seminal cfDNA was compared to BPH patients, revealing a significant difference in the concentration levels of cfDNA in PCa and BPH patient cohorts. A possible cut-off level of 450 ng/ul seminal cfDNA was proposed as able to discriminate between the two distinct groups.…”
Section: Ctdna In Ascitesmentioning
confidence: 99%